Patient-Reported Outcome Measures in Routine Pediatric Clinical Care: A Systematic Review - Bele, Sumedh; Chugh, Ashton; Mohamed, Bijan; Teela, Lorynn; Haverman, Lotte; Santana, Maria J. (Frontiers in Pediatrics, 2020)
Introduction: Integration of PROMs (Patient-reported outcome measures) in routine clinical care is growing but lacks consolidated evidence around its impact in pediatric care. This systematic review aims to evaluate the impact of integrating PROMs in routine pediatric clinical care on various outcomes in pediatric clinical care. Data Sources: MEDLINE, EMBASE, CINAHL, PsychINFO and Cochrane library. Web of Science database was searched selectively to ensure extended coverage. Study Selection: We included longitudinal studies reporting on integration of PROMs in routine pediatric clinical care of chronic diseases. Studies in languages other than English, published prior to the year 2000, and reporting on secondary data were excluded. Data Extraction: Two reviewers independently extracted data from included studies. Extracted data included citation of each study, type of healthcare setting, location of the study, characteristics of patient population, type of chronic disease, name and type of PROM, mode of administration and reported outcomes. Results: Out of 6869 articles, titles and abstracts of 5416 articles and full text of 23 articles were screened in duplicate. Seven articles reporting results from 6 studies met eligibility criteria. Integration of PROMs increased identification and discussion around HRQOL, especially in psychosocial and emotional domains, but showed mixed results with the impact on quality of care. No studies assessed the impact of integrating PROMs on healthcare utilization. Limitations: Due to significant heterogeneity in the studies, a meta-analysis was not conducted. Conclusions: Integrating PROMs could have a positive impact on HRQOL however, further studies are required to determine the impact of PROMs in routine pediatric clinical care.